2015
DOI: 10.1007/s40265-015-0432-8
|View full text |Cite
|
Sign up to set email alerts
|

Current and Emerging Therapeutic Strategies for the Treatment of Meibomian Gland Dysfunction (MGD)

Abstract: Meibomian gland (MG) dysfunction (MGD) is a multifactorial, chronic condition of the eyelids, leading to eye irritation, inflammation and ocular surface disease. Initial conservative therapy often includes a combination of warm compresses in addition to baby shampoo or eyelid wipes. The practice of lid hygiene dates back to the 1950s, when selenium sulfide-based shampoo was first used to treat seborrhoeic dermatitis of the eyelids. Today, tear-free baby shampoo has replaced dandruff shampoo for MGD treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 49 publications
0
71
0
12
Order By: Relevance
“…In refractory cases, procedures including intraductal MG probing, thermal pulsation devices, and intense pulse light therapy may be of benefit. 9596,97 In addition, treatment of blepharitis, including recognition and treatment of demodex blepharitis may remove inciting stimuli. Moreover, addressing other co-morbidities, such as ocular allergies, conjunctivochalasis, exposure keratopathy, and essential blepharospasm are important steps in mitigating patient symptoms.…”
Section: Management Of Patients With Neuropathic Corneal Painmentioning
confidence: 99%
“…In refractory cases, procedures including intraductal MG probing, thermal pulsation devices, and intense pulse light therapy may be of benefit. 9596,97 In addition, treatment of blepharitis, including recognition and treatment of demodex blepharitis may remove inciting stimuli. Moreover, addressing other co-morbidities, such as ocular allergies, conjunctivochalasis, exposure keratopathy, and essential blepharospasm are important steps in mitigating patient symptoms.…”
Section: Management Of Patients With Neuropathic Corneal Painmentioning
confidence: 99%
“…Minosiklinin, antikollajenaz aktivitesi ve anti-enflamatuvar özelliklerinden dolayı RA tedavisinde kullanılabileceği öngörülmekteyken, doksisiklin 100 mg/gün ve minosiklin 50 mg/gün dozlarında ve 2-3 ay süreyle kullanılmasının, hem antienflamatuvar etkileri hem de bakteriyel kolonizasyonu azaltmaları nedeni ile kronik Meibomian bezi disfonksiyonunda uzun süreli iyileşmeye neden olduğu bildirilmiştir [21,22] .…”
Section: Anti-enflamatuvar Etkiunclassified
“…IL-1 and TNF-α) were lower in treated animals, suggesting that omega-3 fatty acids can alter the pro-inflammatory milieu and lessen the signs of dry eye. [91,93,102,113] …”
Section: Ocular Diseasesmentioning
confidence: 99%
“…[114] This particular medical device uses a 12-minute vectored thermal pulsation (VTP) treatment that applies heat to the eyelid while also applying pressure to the outer eyelids to enable the release of meibum (oil like substance found in the tears). [113,115] A clinical trial revealed that LipiFlow was able to improve symptoms of ocular irritation, and subsequently in 2011, the FDA approved LipiFlow as a medical device. [116,117] Although the treatment is an effective therapy for some patients, it is still not widely available due to its high cost.…”
Section: Ocular Diseasesmentioning
confidence: 99%